Performance Determinants - Br Tarigan, Priskanta; B, Mesra (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
This research aims to analyze the influence of work experience and compensation on employee performance, both directly and indirectly through work motivation, at BPJS Ketenagakerjaan Medan Utara and Kisaran branches. The study utilized quantitative methods, collecting data from 80 permanent employees as the sample. The results show that compensation positively and significantly affects employee performance, while work experience indirectly impacts performance through motivation. However, work experience alone does not have a significant direct effect on performance. The findings emphasize the role of motivation as a mediating factor in enhancing employee performance, driven by both compensation and experience.